An Exact Method to Determine the Conductivity of Aqueous Solutions in Acid-Base Titrations - Norma Rodríguez-Laguna; Alberto Rojas-Hernández; María Teresa Ramírez-Silva; Lucero Hernández-García; Mario Romero-Romo (Journal of Chemistry)
Several works in the literature show that it is possible to establish the analytic equations to estimate the volume V of a strong base or a strong acid (Vb and Va, resp.) being added to a solution of a substance or a mix of substances during an acid-base titration, as well as the equations to estimate the first derivative of the titration plot dpH/dV, and algebraic expressions to determine the buffer β capacity with dilution βdil. This treatment allows establishing the conditions of thermodynamic equilibria for all species within a system containing a mix of species from one or from various polyacid systems. The present work shows that it is possible to determine exactly the electric conductivity of aqueous solutions for these Brønsted acid-base titrations, because the functional relation between this property and the composition of the system in equilibrium is well known; this is achieved using the equivalent conductivity λi values of each of the ions present in a given system. The model employed for the present work confirms the experimental outcomes with the H2SO4, B(OH)3, CH3COOH, and H3PO4 aqueous solutions’ titration.